Genetic control of low-density-lipoprotein subclasses - Austin, M A; Krauss, R M (The Lancet (British edition), 1986)
In a study of lipoprotein subclasses in 79 healthy members of sixteen nuclear families evidence was obtained that low-density-lipoprotein (LDL) subclass patterns determined by gradient-gel electrophoresis are influenced by a common allele at a single genetic locus. The estimated frequency of the allele leading to the phenotype characterised by predominance of small, dense LDL subclasses was about 15%. Expression of this phenotype appears to be age dependent, in that most affected subjects in this population were older than 40 years. Although plasma lipid levels were normal in most subjects with this trait, levels of plasma apoprotein B and triglyceride were higher and levels of apoprotein AI and HDL2 lower than in unaffected family members. It is possible that this genetic trait may interact with other genetic or environmental variables in predisposing affected individuals to atherogenic lipoprotein and apoprotein profiles.